2014
DOI: 10.1016/j.neuroimage.2013.12.063
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of spatial functional network connectivity in healthy individuals and schizophrenia patients using independent vector analysis

Abstract: Recent work on both task-induced and resting-state functional magnetic resonance imaging (fMRI) data suggests that functional connectivity may fluctuate, rather than being stationary during an entire scan. Most dynamic studies are based on second-order statistics between fMRI time series or time courses derived from blind source separation, e.g., independent component analysis (ICA), to investigate changes of temporal interactions among brain regions. However, fluctuations related to spatial components over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
171
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 50 publications
5
171
0
Order By: Relevance
“…In addition, we focused on task fMRI data in this study. Recently, IVA has found promising applications for resting-state fMRI data due to superior performance in capturing subject variability over group ICA (Ma et al, 2014;Laney et al, 2015aLaney et al, , 2015bGopal et al, 2015Calhoun and Adali, 2016). In the future, we will extend the proposed method to analyze resting-state complex-valued fMRI data.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, we focused on task fMRI data in this study. Recently, IVA has found promising applications for resting-state fMRI data due to superior performance in capturing subject variability over group ICA (Ma et al, 2014;Laney et al, 2015aLaney et al, , 2015bGopal et al, 2015Calhoun and Adali, 2016). In the future, we will extend the proposed method to analyze resting-state complex-valued fMRI data.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to tensor decomposition, ICAbased analysis extracts subject-specific TCs and/or SMs for emphasizing inter-subject variability. Two such approaches are group ICA (Calhoun et al, 2001(Calhoun et al, , 2008Guo and Pagnonib, 2008;Erhardt et al, 2011;Calhoun and Adali, 2012b;Eloyan et al, 2013;Afshin-Pour et al, 2014) and independent vector analysis (IVA, a kind of joint ICA) (Lee et al, 2008a;Dea et al, 2011;Michael et al, 2014;Ma et al, 2014;Laney et al, 2015aLaney et al, , 2015bGopal et al, 2015Adali et al, 2015). While group ICA provides individual TCs or SMs via ICA of temporally or spatially concatenated multi-subject fMRI datasets, IVA generates individual TCs and SMs via joint ICA of multi-subject fMRI datasets where similar SMs among different subjects were concatenated as source component vectors (SCVs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous work (Kiviniemi et al, 2011) has reported substantial spatial dynamics when doing sliding time window ICA, though that study used low model order ICA decompositions (on average 15 components). In addition, a more recent study (Ma et al, 2014) demonstrated time-varying spatial brain connectivity in HCs and SZs using independent vector analysis (IVA). In contrast with our finding that patients show lower variation of the dynamic graph metrics, that work found significantly more fluctuations of spatial concordance in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, discoveries of structural MRI-based network in schizophrenia can complement studies which show disrupted white matter tracts [3] and functional connectivity [54] between brain regions in the disease [11]. Then, we will present the results of recent researches of sMRI-based network applied in the schizophrenia.…”
Section: Smri-based Brain Network Application In Schizophreniamentioning
confidence: 95%